Hospital reform and staff morale in South Africa: A case study of Dr Yusuf Dadoo Hospital - O.J. Ibeziako; O.N. Chabikuli; S. Olorunju (South African Family Practice)
Objectives: This study explored major factors that influenced staff motivation at a district hospital in South Africa following hospital reforms and comparison of these factors across the two main staff categories.